Retail category management decision support systems for assortment, shelf space, inventory and price planning - Hübner, Alexander; SpringerLink (Online service). (Berlin New York Springer, 2011)
Retail shelf management means cost-efficiently aligning retail operations with consumer demand. As consumers expect high product availability and low prices, and retailers are constantly increasing product variety and striving towards high service levels, the complexity of managing retail business and its operations is growing enormously. Retailers need to match consumer demand with shelf supply by balancing variety (number of products) and service levels (number of items of a product), and by optimizing demand and profit through carefully calibrated prices. As a result the core strategic decisions a retailer must make involve assortment sizes, shelf space assignment and pricing levels. Rigorous quantitative methods have emerged as the most promising solution to this problem. The individual chapters in this book therefore focus on three areas: (1) combining assortment and shelf space planning, (2) providing efficient decision support systems for practically relevant problem sizes, and (3) integrating inventory and price optimization into shelf management
Framework for Retail Demand and Supply Chain Planning -- Empirical Insights, Quantitative Models and Software Applications for Master Category Planning -- Assortment and Shelf Space Planning -- Assortment, Shelf Space and Inventory Planning -- Assortment, Shelf Space and Price Planning
Electronic reproduction.
Keywords: Decision support systems; Retail trade -- Decision making; Retail trade -- Management; Electronic books